Analisis Tokoh dan Penokohan dalam Naskah Drama “ Pada Suatu Hari” Karya Arifin C. Noer sebagai Bahan Pembelajaran Sastra di Sekolah Dasar (Pendekatan Psikologi Sastra) - Mela Yohana Bakkara; Yusra D; Annisa Alin Melia; arifahp2 (Jurnal Pendidikan Dasar, 2025)
This study aims to analyze the characters and characterization in the drama script "Pada Satu Hari" by Arifin C. Noer using a literary psychology approach and explore its relevance as a literary learning material for elementary school students. Arifin C. Noer's work is known for its richness in human values ​​and inner reflection, which are crucial for understanding the motivations and psychological dynamics of the characters. The method used in this study is descriptive qualitative with content analysis techniques. Data were obtained through in-depth reading and identification of the characters' psychological elements, which were then synthesized into teaching materials appropriate to the cognitive and affective development of elementary school students. The results show that the main character experiences an intrapersonal conflict between idealism and social reality. Characterization is complexly depicted through dialogue and actions that reflect a search for self-identity. In the context of elementary school education, the results of this analysis are adapted into teaching materials that emphasize character recognition, empathy, and simple conflict resolution. The novelty of this research lies in the effort to construct the results of a complex literary psychology analysis into applicable drama learning tools for elementary school students. These findings are expected to enrich educators' references in selecting drama texts that are able to build students' emotional intelligence and character through an appreciation of modern realistic literature.